2017
DOI: 10.26524/2017.06.02.4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of two-month training program on anthropometry and VO2max in recreational athletes

Abstract: Abstract:The aim was to evaluate the effect of a two-month training program on some anthropometric characteristics and maximum oxygen consumption (VO2 max) in male and female recreational athletes. Study included 62 participants, 30 males and 32 females. All participants were doing recreational sport, aged from 35 to 50 years old. In order to obtain accurate results, the following instruments were used: measuring tape, InnerScan body composition monitor Tanita BC-532, and "Technogym" treadmill where they were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…These skills consist of defensive tactics, marksmanship training, and the load carriage of body armour and daily accoutrements [ 10 ]. Physical training of police trainees optimizes body composition and improves physical performance measures, such as power and aerobic capacity [ 11 , 12 ]. These improvements can improve health status, protect against injury and illness, and improve occupational performance [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…These skills consist of defensive tactics, marksmanship training, and the load carriage of body armour and daily accoutrements [ 10 ]. Physical training of police trainees optimizes body composition and improves physical performance measures, such as power and aerobic capacity [ 11 , 12 ]. These improvements can improve health status, protect against injury and illness, and improve occupational performance [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Body composition assessment is often used for members of the police force as an important tool for evaluation of physical fitness and health status [ 1 , 2 , 3 ]. Body composition is a valuable assessment since it is the result of various factors such as diet, stress, the amount of physical activity, and other daily habits [ 4 , 5 , 6 , 7 ]. Therefore, regular screening of body composition may provide a timely information on changes produced by these factors.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have found that trainees' fitness can be improved through a good physical training program (Crawley, Sherman, Crawley, & Cosio-Lima, 2016;Dimitrijević, Koropanovski, Dopsaj, Vučković, & Janković, 2014;Stojković, Čvorović, Jeknić, & Kukić, 2017). Stojković et al (2017) found that two months of training, three times per week for 90 minutes, significantly improved body weight, body fat mass and waist circumference as well as VO 2 max in men.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have found that trainees' fitness can be improved through a good physical training program (Crawley, Sherman, Crawley, & Cosio-Lima, 2016;Dimitrijević, Koropanovski, Dopsaj, Vučković, & Janković, 2014;Stojković, Čvorović, Jeknić, & Kukić, 2017). Stojković et al (2017) found that two months of training, three times per week for 90 minutes, significantly improved body weight, body fat mass and waist circumference as well as VO 2 max in men. Crawley et al (2016) found that police trainees performing a 16-week exercise program, three 60-minute sessions per week, of aerobic, plyometric, body weight and resistance exercises, significantly improved their upper-body peak power after the first eight weeks of the program and only minimal changes occurred after the second eight weeks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation